Pemikiran Abu Daud Tentang Penulisan Hadis - Barsihannor Annur (Universitas Islam Negeri Alauddin, 2013)
Abu Daud is a famous Islamic scholar in hadis field who has collected hadis in his book called Sunan Abi Daud. In addition, he also released many written works that we are now still able to read and study parts of them. Abu daud has got many appreciations from Islamic scholar either in the form of comment or praise because of his hadis books which are considered having good standard and quality. Some Islamic scholars, however, criticize his book for including several daif hadis.